Understanding prices at art auctions - Noll, Laura (online, 2022)
Since the growth of the art market into a capitalized global art industry, public and academic discourse on art auctions has been dominated by record prices. Despite the financial potential of art auctions as well as the public and academic interest in art, understanding of auction prices is limited. Price intransparency is exacerbated by contrasting approaches in theory and practice: Theory is dominated by quantitative studies that measure the effects of individual factors that determine prices. The literature body is broad but interdisciplinary and fragmented. Practice emphasizes the inadequacy of quantification. Instead, valuation relies on artwork-related characteristics and reference prices. To date, there is no comprehensive theory of auction prices that combines both perspectives. To fill this gap, the author conducts three studies: A systematic literature review (Study 1) of 100 high-impact journal articles summarizes the (quantitative) knowledge on price determinants. Eleven in- depth expert interviews (Study 2) clarify how these determinants and other factors that are unquantifiable or difficult to quantify influence prices. Two digital focus groups (Study 3) resolve remaining ambiguities between theory and practice and elucidate the role of marketing for auction prices. The result is a conceptual framework for the auction price mechanism that accounts for quantifiable and unquantifiable or difficult-to-quantify factors and reveals the underlying dynamics of the art market. The thesis is of high theoretical and practical relevance: It provides an empirical basis for valuation and price explanation. On this basis, it points to promising avenues for future research in various disciplines and suggests practical implications for different stakeholders in the art market. Beyond the art market, this thesis inspires marketing and pricing in other industries.
urn:nbn:ch:bel-2340531
Keywords: Graue Literatur; Hochschulschrift; Kunst; Kunstmarkt; Kunstauktion; Auktion; Wert; Preis; Marktmechanismus; Preispolitik; Marketing; Kulturwirtschaft; marketing; art auction; price mechanism; Preismanagement; auction; price management; art economics; Art; value; art market; cultural economics; Preismechanismus; price; Kulturökonomie